Razrešitev sodnika - Fajdiga, Mohor (Pravnik, 2023)
The new draft judicial service act (the JSA-1) envisages an abolition of the disciplinary dismissal of a judge. Under the new rules, the termination of a judge’s office would be primarily due to a negative evaluation of judicial service. The proposed amendment relies on four false assumptions. First, the draft wrongly regards disciplinary proceedings as the predominant means for securing judicial accountability in Slovenia. Second, the evaluation of judicial service would mostly not follow a final disciplinary decision as the draft envisages. Third, contrary to the views of the sponsor of the new bill, the Slovenian Constitution allows judges to be dismissed without the involvement of the National Assembly. Forth, Slovenia cannot freely regulate the matters at hand, as the draft wrongly assumes, but is bound by certain international and EU law obligations. Because of these false assumptions, the draft, which was meant to enhance judicial independence, paradoxically works to its detriment.
Keywords: pravna ureditev; sodniki; sodstvo; uvodniki